Supplement for an academic degree and academic title for employees of higher education institutions: issues of legal regulation - Huk, Bohdan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article raises the issue of legal regulation of the establishment of supplements for an academic degree and academic title to employees of higher education institutions. The goal is to research the mechanism of legal regulation of determining the appropriateness of an academic degree and/or academic title to the profile of the employees' activity in order to establish the appropriate additional payment guaranteed to them by law. An analysis of scientific views on the system of remuneration in the field of education was carried out. The legal guarantees of the additional salary of a scientific and pedagogical worker in the form of mandatory supplement for an academic degree and/or academic title have been studied. It is emphasized that the presence of an academic degree or academic title is one of the guarantees of a higher education institution obtaining a license to carry out educational activities of the appropriate type. The conflicting provisions of the legislation on education and on labour remuneration are analysed, which give the employer the opportunity, under certain conditions, to refuse a scientific and pedagogical worker to establish an additional payment for an academic degree and/or academic title. The judicial practice of resolving labour disputes regarding the employer's refusal to establish a supplement for an employee's academic degree or academic title is analysed. Attention is focused on the legal grounds for the mandatory establishment of supplements to employees for academic degrees and/or academic titles, controversial regulatory provisions regarding the possibility of establishing supplements when the academic degree or academic title does not match the employee's activity profile. There is a well-founded need for a normative consolidation of the criteria for determining the appropriateness of an academic degree and/or academic title of an employee's activity profile. Additional arguments have been traced regarding the legal possibility of establishing a supplement for an academic degree and/or academic title to a scientific and pedagogical worker who, along with teaching or scientific work, is engaged in the organization of the educational or scientific process, holds administrative positions in units whose activities are aimed at organizational and methodical support for educational process.Conclusions were made that a scientific and scientific-pedagogical worker of a scientific institution or higher education institution has the right to supplement for an academic degree and academic title regardless of the activity profile of the department or educational or scientific programme without determining their compliance. Proposals regarding possible ways to overcome legal conflicts on this issue, determination of possible criteria for establishing the correspondence of an academic degree and/or academic title to an employee's activity profile as a basis for establishing a supplement, provided for by the current legislation of Ukraine, are substantiated.